2010
DOI: 10.1051/cocv/2010012
|View full text |Cite
|
Sign up to set email alerts
|

Discrete mechanics and optimal control: An analysis

Abstract: Abstract. The optimal control of a mechanical system is of crucial importance in many application areas. Typical examples are the determination of a time-minimal path in vehicle dynamics, a minimal energy trajectory in space mission design, or optimal motion sequences in robotics and biomechanics. In most cases, some sort of discretization of the original, infinite-dimensional optimization problem has to be performed in order to make the problem amenable to computations. The approach proposed in this paper is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
133
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 144 publications
(136 citation statements)
references
References 68 publications
3
133
0
Order By: Relevance
“…Then, the order of the discrete Lagrangian and the discrete virtual work is given by the order of the quadrature rule in use. In [25], (Ober-Blöbaum et al, submitted) it is shown for DMOC (unconstrained dynamics) that a discrete Lagrangian and discrete virtual work of order lead to an optimal control scheme of order . ‡ That means, the state and control trajectories as well as the Lagrange multipliers resulting from the Pontryagin maximum principle are approximated with an accuracy of O(h ).…”
Section: Accuracy and Efficiencymentioning
confidence: 99%
See 3 more Smart Citations
“…Then, the order of the discrete Lagrangian and the discrete virtual work is given by the order of the quadrature rule in use. In [25], (Ober-Blöbaum et al, submitted) it is shown for DMOC (unconstrained dynamics) that a discrete Lagrangian and discrete virtual work of order lead to an optimal control scheme of order . ‡ That means, the state and control trajectories as well as the Lagrange multipliers resulting from the Pontryagin maximum principle are approximated with an accuracy of O(h ).…”
Section: Accuracy and Efficiencymentioning
confidence: 99%
“…Then the body's Euler tensor with respect to the center of mass can be related to the inertia tensor J via E = 1 2 (tr J)I−J, where I denotes the 3×3 identity matrix. The principal values of the Euler tensor, E i , together with the body's total mass M are ingredients in the rigid-body's constant symmetric positive-definite mass matrix The angular momentum of the rigid body can be computed as L = u×p +d I ×p I (25) where summation convention is used to sum over the repeated index I . Null space matrix: An account of rigid-body dynamics is given in [36,42] where also the null space matrix…”
Section: Optimal Control For Rigid-body Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…In most applications, optimal control problems have to be solved by numerical methods. In this contribution, we will use DMOC (Discrete Mechanics and Optimal Control, [2]), a direct optimal control method for mechanical systems. (Un)stable Manifolds of the Natural Dynamics The natural, i.e.…”
Section: Introductionmentioning
confidence: 99%